On the time spent preparing grant proposals: an observational study of Australian researchers - Nicholas Graves; Adrian G Barnett; Philip Clarke; Danielle L Herbert (BMJ Open)
Objective To estimate the time spent by the researchers for preparing grant proposals, and to examine whether spending more time increase the chances of success.Design Observational study.Setting The National Health and Medical Research Council (NHMRC) of Australia.Participants Researchers who submitted one or more NHMRC Project Grant proposals in March 2012.Main outcome measures Total researcher time spent preparing proposals; funding success as predicted by the time spent.Results The NHMRC received 3727 proposals of which 3570 were reviewed and 731 (21%) were funded. Among our 285 participants who submitted 632 proposals, 21% were successful. Preparing a new proposal took an average of 38 working days of researcher time and a resubmitted proposal took 28 working days, an overall average of 34 days per proposal. An estimated 550 working years of researchers' time (95% CI 513 to 589) was spent preparing the 3727 proposals, which translates into annual salary costs of AU$66 million. More time spent preparing a proposal did not increase the chances of success for the lead researcher (prevalence ratio (PR) of success for 10 day increase=0.91, 95% credible interval 0.78 to 1.04) or other researchers (PR=0.89, 95% CI 0.67 to 1.17).Conclusions Considerable time is spent preparing NHMRC Project Grant proposals. As success rates are historically 20–25%, much of this time has no immediate benefit to either the researcher or society, and there are large opportunity costs in lost research output. The application process could be shortened so that only information relevant for peer review, not administration, is collected. This would have little impact on the quality of peer review and the time saved could be reinvested into research.